Laporan Kasus: Dentinogenesis Imperfekta - Fadli Ashar; Evellyn Islami Abdurokhman (Fakultas Kedokteran Gigi Universitas Jember, 2019)
Dentinogenesis imperfecta is the one of most common hereditary disorder of dentin formation, especially at histodifferentiation stage. It reported have to an incidences of 1 in 8000. Dentinogenesis imperfecta is an autosomal dominant, affecting both the formation and mineralizatin of dentin. CASE: A 20-year-old female patient came to integrasi A RSGMP UNSOED with crown fracture of anterior teeth 11, after eating a solid food. A permanent filling was conducted on 21 with the same cause one year ago. Intraoral examination showed attrition, yellowish and translucent on both maxillary and mandibullary teeths. Radiography showed that obliterated pulp chamber and shrinked root canal. Porcelain fused to metal crown was planned for this case. Conclusion: Dentinogenesis imperfecta is a hereditary disorder of tooth development. It caused the teeth to be discoloured (blue-grey or yellow-brown color), and fragile. Treatment planning for patient with dentinogenesis imperfecta is restorative treatment that can be apply to deciduous or permanent teeth, because exposed dentin will increase the risk of caries and infection.